Monosomy 3pter-p25.3 and Trisomy 1q42.13-qter in a Boy With Profound Growth and Developmental Restriction, Multiple Congenital Anomalies, and Early Death - Chumei Li; Vikas Mahajan; Jia-Chi Wang; Bosco Paes (Pediatrics and Neonatology)
Albeit rare, 3pter-p25 monosomy or 1q42-qter trisomy syndromes have been documented in the literature. Here, we report a unique case with a combination of 3pter-p25 monosomy and 1q42-qter trisomy, delineated by array comparative genomic hybridization analysis. The proband was a newborn male with multiple congenital anomalies that included brain malformation, ocular anomalies, trachea-laryngomalacia, cardiac defects, intestinal malrotation, and cutaneous findings in conjunction with biochemical anomalies, profound growth and developmental restriction, and early death. To our knowledge, this is the first case report of this unique chromosomal imbalance.